2020
DOI: 10.1155/2020/7408508
|View full text |Cite
|
Sign up to set email alerts
|

Depression Prevalence in Neuropathic Pain and Its Impact on the Quality of Life

Abstract: Introduction. The management of neuropathic pain remains complex, generally because of the psychiatric comorbidity that is often underdiagnosed. The objectives of our work were to determine the link between depression and the characteristics of NP on the one hand and quality of life on the other hand, in a sample of subjects consulting for neuropathic pain (NP) regardless of etiology. Methods. We conducted a cross-sectional study involving 61 neuropathic pain consulting patients in whom we assessed five parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 37 publications
(43 reference statements)
6
50
1
1
Order By: Relevance
“…These resultsare in line with previous studies in other countries. For example, in Tunisian patients with PDN, depression, and anxiety rates are 65.6% and 73.7% (18).Also, in the USA, the anxiety rate in PDN is reported to be 57% which is close to our results (38).Also, various researches in chronic pain found that sleep disturbances rate range between 50% to 80% (39,40). So, in Iranian patients with PDN, sleep disturbances are higher than in almost all countries.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…These resultsare in line with previous studies in other countries. For example, in Tunisian patients with PDN, depression, and anxiety rates are 65.6% and 73.7% (18).Also, in the USA, the anxiety rate in PDN is reported to be 57% which is close to our results (38).Also, various researches in chronic pain found that sleep disturbances rate range between 50% to 80% (39,40). So, in Iranian patients with PDN, sleep disturbances are higher than in almost all countries.…”
Section: Discussionsupporting
confidence: 83%
“…In another study, painrelated factors reduced QoL in patients with diabetes (33).Furthermore, Cherif et al (2020) found that depression symptoms extensively reduced Qol in patients with PDN. Moreover, they found that depression was positively correlated with pain severity (18).Also, Pain Catastrophizing Is Independently Associated with Qol in medical contexts (34).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations